Identifying and developing junior elite athletes - Holmes, M. J.
Most of the components we started with have been given some attention: 1.Have a clear view of what your elite program is or is going to be 2.If possible, develop a squad which the promising youngster can feed into 3.Get them up to speed - elite high jump is not a long term process 4.Train hard, but rest long 5.Know the system: the selectors, the selection criteria and process, national coaches, event coaches, team managers Establish or reaffirm your principles (but re-appraise them at the end of each season). Question the components of the event and their demands. Hopefully, have a good technical model in place by the age of 16 - early success based on conditioning does the athlete's long term development a great disservice. The purpose of conditioning up to that stage is education, familiarity and preparation for later training regimes. Bear in mind that the elite junior in the early stages is more likely to be able to deal with basic fitness conditioning rather than plyometrics and strength work; increase the load gradually and progressively. In summary, if you have taken an athlete through from novice, it is unlikely that the 'same but more' is going to be the answer. The emphasis is going to switch from a skill base to a conditioning regime, almost overnight in many cases. You do not actually need to be a high jump coach to do that!